Coulomb-nuclear dynamics in the breakup of the weakly bound Li 8 nucleus - Mukeru, B.; Lubian, J.; Tomio, Lauro [UNESP] (American Physical Society (APS), 2022)
A detailed study of total, Coulomb, and nuclear breakup cross sections dependence on the projectile ground-state binding energy ɛb is presented by considering the Li8+C12 and Li8+Pb208 breakup reactions. To this end, apart from the experimental one-neutron separation energy of Li8 nucleus (ɛb=2.03MeV), lower values of ɛb down to ɛb=0.01MeV, are also being considered. It is shown that all breakup processes become peripheral as ɛb→0.01MeV, which is understood as due to the well-known large spacial extension of ground-state wave functions associated to weakly bound projectiles. The Coulomb breakup cross section is found to be more strongly dependent on ɛb than the nuclear breakup cross section, such that the Coulomb breakup becomes more significant as ɛb decreases, even in a naturally nuclear-dominated reaction. This is mainly due to the long-range nature of the Coulomb forces, leading to a direct dependence of the Coulomb breakup on the electromagnetic transition matrix. It is also highlighted the fact that the nuclear absorption plays a minor role for small binding when the breakup becomes more peripheral.